Administration of antigenically distinct influenza viral particle combinations as an influenza vaccine strategy. - Xinyu Zhu; Zhaochen Luo; Rebecca A Leonard; Cait E Hamele; Rachel L Spreng; Nicholas S Heaton (PLoS Pathogens)
One approach for developing a more universal influenza vaccine is to elicit strong immune responses against canonically immunosubdominant epitopes in the surface exposed viral glycoproteins. While standard vaccines typically induce responses directed primarily against mutable epitopes in the hemagglutinin (HA) head domain, there are generally limited or variable responses directed against epitopes in the relatively more conserved HA stalk domain and neuraminidase (NA) proteins. Here we describe a vaccine approach that utilizes a combination of wildtype (WT) influenza virus particles along with virus particles engineered to display a trimerized HA stalk in place of the full-length HA protein to elicit both responses simultaneously. After initially generating the "headless" HA-containing viral particles in the A/Hawaii/70/2019 (HI/19) genetic background and demonstrating the ability to elicit protective immune responses directed against the HA-stalk and NA, we co-formulated those virions with unmodified WT viral particles. The combination vaccine elicited "hybrid" and protective responses directed against the HA-head, HA-stalk, and NA proteins in both naïve and pre-immune mice and ferrets. Collectively, our results highlight a potentially generalizable method combining viral particles with differential antigenic compositions to elicit broader immune responses that may lead to more durable protection from influenza disease post-vaccination.